Particle size and morphological characterization of cosmetic emulsified systems by Optical Coherence Tomography (OCT) - Paula Souza Prestes; Daniela D'Almeida Peres; Anderson Zanardi de Freitas; Vladi Olga Consiglieri; Telma Mary Kaneko; Maria Valéria Robles Velasco; André Rolim Baby
ABSTRACT The physicochemical attributes of emulsified systems are influenced by the characteristics of their internal phase droplets (concentration, size and morphology), which can be modified not only by the formulation components, but also by the analytical methodology employed. Thus, the aim of this work involved the physicochemical characterization of cosmetic emulsions obtained from different surfactants, as well as the introduction of the optical coherence tomography (OCT) as the analytical technique employed for the morphological characterization and particle size determination of the formulations. Three emulsions were prepared, differing at the type and concentration of the surfactant used, and their droplet sizes were evaluated through optical microscopy, laser diffraction and OCT. The microscopic analysis and the laser diffraction techniques provided an average particle size minor than 6.0 µm, not detected by the OCT technique, which could identify only bigger particles of the emulsified systems' internal phase. The results testify that OCT was suitable for the morphological characterization of cosmetic emulsions; however, the technique needs to be improved to ensure a better sensitivity in the analysis of smaller particles.